An Experimental Method in Juxtaposing Draft Picks and Active Players. Issue 1 (24th April 2021) - Chandrakumaran, Jemuel
Abstract : Trading picks are a common transaction that is observed in sporting leagues that conduct player drafts. However, with its evolution, current iterations allow for the trading of picks and players, which in turn raises questions about valuing such trades. This study proposes a pick valuation system using survival analysis techniques, which was further extended to value players who were already enlisted. The model proved to be viable, allowing to evaluate trades involving both picks and players.